2008
DOI: 10.1253/circj.72.1
|View full text |Cite
|
Sign up to set email alerts
|

Redox Regulation in the Extracellular Environment

Abstract: Molecular oxygen is involved in the oxidation of substrates used to produce energy; however, normal metabolism can also generate harmful (bio)chemical byproducts. These deleterious products are partially reduced forms of oxygen, and include free radicals such as superoxide anion radical, hydroxyl radical, or highly oxidizing non-radical species such as hydrogen peroxide (H2O2) and lipid peroxides, which are collectively known as ROS. 1 ROS typically derive from normal metabolism, activated leukocytes, and ambi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
102
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(105 citation statements)
references
References 251 publications
2
102
0
1
Order By: Relevance
“…These data indicated that an oxidative status promotes SR-BI-mediated HDL binding and cholesteryl ester uptake, whereas a reductive status suppresses SR-BImediated HDL binding and cholesteryl ester uptake. Note that the extracellular compartment is an oxidative environment and that H 2 O 2 is one of the major oxidants in the extracellular compartment, which presents as high as submillimole per liter levels ( 37 ). Our data suggest that physiological relevant levels of H 2 O 2 can promote SR-BI-mediated HDL binding and cholesteryl ester uptake.…”
Section: Changes In Redox Status Regulated Sr-bi-mediated Hdl Bindingmentioning
confidence: 69%
See 2 more Smart Citations
“…These data indicated that an oxidative status promotes SR-BI-mediated HDL binding and cholesteryl ester uptake, whereas a reductive status suppresses SR-BImediated HDL binding and cholesteryl ester uptake. Note that the extracellular compartment is an oxidative environment and that H 2 O 2 is one of the major oxidants in the extracellular compartment, which presents as high as submillimole per liter levels ( 37 ). Our data suggest that physiological relevant levels of H 2 O 2 can promote SR-BI-mediated HDL binding and cholesteryl ester uptake.…”
Section: Changes In Redox Status Regulated Sr-bi-mediated Hdl Bindingmentioning
confidence: 69%
“…Different from a reducing environment in the intracellular compartment, the extracellular compartment is highly oxidative ( 37 ). Cysteinyl residues in the extracellular compartment can undergo a variety of oxidative modifi cations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EC-SOD is found in most tissues, but higher amounts of EC-SOD are present in vascular tissue, while EC-SOD is only present in small amounts in the liver, brain and heart compared with Cu, Zn-SOD and Mn-SOD. [15][16][17] EC-SOD is the only isozyme of SOD that is expressed extracellularly, binding to tissues via its heparin-binding domain to give affinity to heparan sulfate proteoglycans on the cell surface, in basal membranes and in the extracellular matrix. 14,18) The presence of EC-SOD on the vascular wall might have an important protective effect against the ROS generated in the vascular system.…”
mentioning
confidence: 99%
“…It is now recognized that sustained hyperglycemia in diabetic patient, causes protein glycation and generates free radicals through autooxidation and polyol pathways (Ramakrishna and Jailkhani, 2008;Sharma et al, 2003). High levels of free radicals with concurrent decline of antioxidant defense mechanism may lead to damage of cellular organelles and enzymes (Ottaviano et al, 2008). This can culminate in increased lipid peroxidation and development of insulin resistance, which may consequently promote the development of complications of diabetes mellitus (Demozay et al, 2008).…”
Section: Introductionmentioning
confidence: 99%